2018
DOI: 10.3233/blc-170152
|View full text |Cite
|
Sign up to set email alerts
|

Toward Personalised Liquid Biopsies for Urothelial Carcinoma: Characterisation of ddPCR and Urinary cfDNA for the Detection of the TERT 228 G>A/T Mutation

Abstract: Background:TERT promotor mutations are present in >75% of bladder tumours; these mutations are also detectable in urine. Previous studies have used urinary pellet DNA, and semi-quantitative methods unsuitable for detecting very low mutant allele frequencies.Objective:In this proof-of-principle study we use ddPCR to count the DNA molecules with wt and mutant TERT sequences in urinary cfDNA from patients whose bladder cancers harbour TERT mutations.Methods:Urinary cfDNA prepared from the urine from 104 bladder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
4
35
1
Order By: Relevance
“…Using amplicon sequencing, tumour SMs were detected in 78% of cfDNAs, and cfDNA and cpDNA MAFs were correlated, as previously demonstrated [29]. There was a small (5%) but significant (P < 0.001) increase in average MAF in cfDNA relative to cpDNA.…”
Section: -Gene Panel For Urinary Ubc Diagnosissupporting
confidence: 78%
“…Using amplicon sequencing, tumour SMs were detected in 78% of cfDNAs, and cfDNA and cpDNA MAFs were correlated, as previously demonstrated [29]. There was a small (5%) but significant (P < 0.001) increase in average MAF in cfDNA relative to cpDNA.…”
Section: -Gene Panel For Urinary Ubc Diagnosissupporting
confidence: 78%
“…To extract 1 ng of cfDNA from urine with our protocol costs $2.7 with ZQ, while QC and MM cost $7.6 and $5.0, respectively. ZQ has been widely used for urinary cfDNA isolation in multiple studies of liquid biopsies for urologic malignancies [11,14,33]. In fact, ZQ is designed for both cfDNA and cellular DNA.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies on urinary pellet DNA and urine supernatant cfDNA from UBC patients. Various mutations could be detected in urinary pellet DNA, and in urinary cfDNA from UBC. Russo et al reported that 92% of urinary cfDNA analyzed by ddPCR showed the same mutational result as that from the matched tumor tissue analyzed by NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Various mutations could be detected in urinary pellet DNA, and in urinary cfDNA from UBC. Russo et al reported that 92% of urinary cfDNA analyzed by ddPCR showed the same mutational result as that from the matched tumor tissue analyzed by NGS. Togneri et al reported that urinary cfDNA of UBC patients has a higher tumor genomic burden and greater detection potential as a genomic biomarker (90%) than urinary pellet DNA (61%).…”
Section: Discussionmentioning
confidence: 99%